Impact of the COVID-19 pandemic on tobacco product consumption and behavioral patterns from a low-middle income country perspective: A qualitative study - Freire, Ana Paula Coelho Figureira; Foch, Eric; Medina, Bruna Aparecida Santos; Uzeloto, Juliana Souza; Leite, Marceli Rocha; de Alencar Silva, Bruna Spolador [UNESP]; Okoshi, Marina Politi [UNESP]; Pacagnelli, Francis Lopes (European Publishing, 2025)
INTRODUCTION Previous studies investigating socioeconomic status and tobacco consumption during the COVID-19 pandemic were survey-based. To extend knowledge beyond prevalence rates and trends of tobacco consumption, qualitative research is needed to identify individual’s experiences. There is a critical gap within this context, particularly in low-middle income countries. The aim of the study was to perform a qualitative analysis on consumption patterns of tobacco users from a low-middle income country during the COVID-19 pandemic, and to identify factors influencing motivation to quit tobacco products during the pandemic and the perceptions of self-risk for complications of tobacco consumption and COVID-19. METHODS A qualitative study was conducted in São Paulo, Brazil in September 2020. We used a focus group with semi-structured interviews. Participants were invited to answer questions about behavioral and consumption patterns of tobacco products during early stages of COVID-19 pandemic. Two investigators independently performed triangulation of content of the transcripts. Data were analyzed using inductive content analysis. RESULTS Eighteen participants were evaluated (66.7% males) with mean age 34.1 ± 14.9 years. Many participants presented high levels (33.3%) of nicotine dependence. Thematic analysis of participants’ narratives resulted in two themes: Theme 1: Behavioral and psychological factors impacting consumption; and Theme 2: Consumption patterns, dependence, and information. Open-coding process resulted on four codes: 1) Behavioral and lifestyle changes; 2) Psychological and motivational factors; 3) Consumption patterns and dependence; and 4) Information exposure and awareness. Nine categories were generated from the codes. CONCLUSIONS Behavioral and consumption patterns varied significantly in tobacco users in Brazil during the early stages of the COVID-19 pandemic, ranging from increases to no changes. Individuals consuming tobacco products showed awareness about the harmful effects of smoking and COVID-19 complications.
Keywords: COVID-19 virus infection; pandemics; smoking; smoking behaviors; smoking habits